Asaru īpašību modelēšana kontaktlēcu slapināšanas pētījumiem - Jankūns, Armands (Latvijas Universitāte, 2011)
Bakalaura darbs ir uzrakstīts latviešu valodā uz 30 lappusēm, satur 16 attēlus, 4 tabulas un 57 atsauksmes uz literatūras avotiem. Atslēgas vārdi: sausās acs, asaru plēvīte, kontaktlēcas, kontakta leņķis. Darba mērķis :Noteikt dažādu kontaktlēcu firmu un materiālu slapināšanos atkarībā no asaru īpašībām. Materiāli: Eksperimentā tika izmantoti divi šķīdumi, kas tika izveidoti balstoties uz spraiguma koeficenta lielumu asaru plēvei Vesela cilvēka acī(43,6 +/- 2,7 mNm) un Sausajā acī(49.6 +/- 2.2 mN/m) . Un ar šiem šķīdumiem tika testētas sekojošās kontaktlēcas: oBAUSCH & LOMB PureVision™ (balafilcon A) oCooper Vision - Biofinity (comfilcon A) oBAUSCH & LOMB SofLens (alphafilcon A) oCooper Vision – Frequency® 55 (methafilcon A) Metodika: Virsmas spraigums mērīts ar Piliena metodi. Mitrināšanas leņķis tika noteikts ņemot mikroparauga fotogrāfijas un apstrādājot tās ar programmatūru. Rezultāti un analīze: visu četru kontaktlēcu kontakta leņķi ir zonā zem 90 grādiem, kas liecina par labu kontaktlēcas slapināšanās spēju. Visaugstākā mitrināšanās spēja ir novērojama tieši hidrogēla grupas kontaktlēcām it īpaši Frequency 55 kontaktlēcai, savukārt zemākā mitrināšanās spēja ir B&L Purevision silikonhidrogēla grupas kontaktlēcai.

Bachelor thesis is written in Latvian. It contains 36 pages, 19 figures, 2 equations, 9 appendices and 25 references. Keywords: color vision, color vision deficiency, color vision tests, pseudoisochromatic tests and illumination. Purpose: qualify and compare performance of clinical tests under different illumination. Subjects: 14 subjects (average age 27, amplitude 18-55 years) with color vision deficiency, without eye or overall organic illnesses took part in experiment. Methods: Color vision testing with Ishihara, Rabkin and Farnsworth D15 test was made to 3 different illuminations (incandescent lamp, natural day light and luminescent bulb). Results: Best sensitivity for people with M cone defect to Ishihara test was measured by luminescent bulbs and natural day light conditions, with L – to artificial light sources; to Rabkin test with M – to natural day light, with L – to incandescent lamp. Average sensitivity for Ishihara test was measured under incandescent lamp, natural day light and luminescent bulb and the results are 0,87, 0,90 and 0,93 respectively, but for Rabkin test - 0,76, 0,73 and 0,74. Calculated specificity for Ishihara test is 1,00 independent of illumination; for Rabkin test – under incandescent lamp and natural day light of value 0,99, and under luminescent bulb – 1,00. Classifications for Ishihara and Farnsworth D15 tests is variable to different illumination. Conclusions: Under incandescent lamp illumination Ishihara and Farnsworth D15 tests might incorrectly classify color vision defects. Rabkin test can make correct classification of color vision defects under different illuminations. Average sensitivity for Ishihara test is higher than for Rabkin`s. Best sensitivity for Ishihara test was measured under luminescent bulb conditions, for Rabkin – with incandescent lamp. Luminescent bulb and natural day light conditions provide similar results for Farnsworth D15 test.
Modeling of tear properties for contact lens wetting research
Keywords: Fizika